A MINI REVIEW ON PROPERTIES, MECHANISM OF ACTION, PHARMACOKINETIC AND PHARMACODYNAMICS AND ANALYTICAL METHODS OF CARIPRAZINE - SHRIVASTAVA, ALANKAR; AGGARWAL, RADHIKA; SINGH, RISHI PRATAP; KHABIYA, RAKHI (International Journal of Applied Pharmaceutics, 2023)
Cariprazine (CPZ) being a “D2/D3 receptor partial agonist” is used for schizophrenia treatment. CPZ illustrate different functional study at “dopamine receptors depending on the assay system”. This study elaborate review summarizes the structure–activity relationship (SAR), Mechanism of action (MOA), pharmacokinetics, pharmacodynamics and analytical methods published. CPZ was found to be more effective than risperidone. It was analogus with a remarkably longer time to deteriorate than inactive drug in a long-term, phase III,-deteriorate prevention study. This study elaborate the activating and solemn or sedative properties of first-line oral second generation antipsychotics by explore the rates of adverse effect in product labelling for the indications of schizophrenia and ancillary treatment of major depressive disorder (MDD). The common adverse events reported were extrapyramidal disorder, insomnia, dizziness, solemn, anxiety, vomiting and constipation in “fixed dose study of tested 1.5, 3.0, and 4.5 mg/day”. The presented review explains about biological properties, pharmacokinetics, pharmacodynamics, and analytical methods of CPZ.